2000
DOI: 10.4049/jimmunol.164.11.5788
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Recognition of an Arthritic Peptide and a Foreign Epitope on Distinct MHC Molecules by a Single TCR

Abstract: KRN TCR transgenic T cells recognize two self-MHC molecules: a foreign peptide, bovine RNase 42–56, on I-Ak and an autoantigen, glucose-6-phosphate isomerase 282–294, on I-Ag7. Because the latter recognition event initiates a disease closely resembling human rheumatoid arthritis, we investigated the structural basis of this pathogenic TCR’s dual specificity. While peptide recognition is altered to a minor degree between the MHC molecules, we show that the receptor’s cross-reactivity critically depends upon a T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
65
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 42 publications
0
65
1
Order By: Relevance
“…This implies that mutants evade immune system detection more easily as an epitope becomes more similar to self peptides, which in turn suggests that the immune system could drive pathogens to express epitopes that mimic self. These "molecular mimics" could either trigger autoimmune responses by activating T cells that cross-react to a self peptide [36,37] or evade immune surveillance. …”
mentioning
confidence: 99%
“…This implies that mutants evade immune system detection more easily as an epitope becomes more similar to self peptides, which in turn suggests that the immune system could drive pathogens to express epitopes that mimic self. These "molecular mimics" could either trigger autoimmune responses by activating T cells that cross-react to a self peptide [36,37] or evade immune surveillance. …”
mentioning
confidence: 99%
“…However, once the pathogenic antibodies have been elicited by the autoimmune reaction, there is no further requirement for lymphoid cells, and the antibodies alone can transfer full-blown arthritis to naive lymphocyte-deficient hosts (5,6). Studies of the K/BxN model also indicated that ubiquitous antigens can be the target of arthritogenic antibodies: those in K/BxN mice recognize the widespread glycolytic enzyme glucose-6-phosphate isomerase (GPI) (7)(8)(9). Does GPI also serve as a target in human diseases?…”
mentioning
confidence: 99%
“…Disease incidence is 100% in BxN mice with the KRN Tg, whereas no disease is detected in Tg(Ϫ) BxN mice (1). KRN T cells recognize a peptide from the glycolytic enzyme glucose-6-phosphate-isomerase (GPI) bound to I-A g7 (3,4). B cells from these mice also recognize GPI as an autoantigen (3).…”
mentioning
confidence: 99%